Proceedings of the Third ACL-SIGSEM Workshop on Prepositions - Prepositions '06 2006
DOI: 10.3115/1621431.1621436
|View full text |Cite
|
Sign up to set email alerts
|

Semantic interpretation of prepositions for NLP applications

Abstract: The proper interpretation of prepositions is an important issue for automatic natural language understanding. We present an approach towards PP interpretation as part of a natural language understanding system which has been successfully employed in various NLP tasks for information retrieval and question answering. Our approach is based on the so-called Multi-Net paradigm, a knowledge representation formalism especially designed for the representation of natural language semantics. The paper describes how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…Hence in text preprocessing, when the subject indicates that the corpus may have stopword-formed phrases, n-gramming should be done first to preserve the semantic information of these phrases. Moreover, if the NLP application involves dependency parsing or semantic reasoning, we have to be careful in removing stopwords, especially prepositions (Hartrumpf, Helbig, and Osswald 2006). For example, the sentence "The box is in the house, and the toy is in the box."…”
Section: Known Issues With Removing Stopwordsmentioning
confidence: 99%
“…Hence in text preprocessing, when the subject indicates that the corpus may have stopword-formed phrases, n-gramming should be done first to preserve the semantic information of these phrases. Moreover, if the NLP application involves dependency parsing or semantic reasoning, we have to be careful in removing stopwords, especially prepositions (Hartrumpf, Helbig, and Osswald 2006). For example, the sentence "The box is in the house, and the toy is in the box."…”
Section: Known Issues With Removing Stopwordsmentioning
confidence: 99%
“…Despite all these studies, Hartrumpf et al (2006) recalled that linguistic studies on preposition semantics have not obtained much impact on NLP applications. Litkowski and Hargraves (2005) presented The Preposition Project, which stores information of English preposition senses to be used in NLP with FrameNet 2 .…”
Section: Preposition Disambiguation In Nlpmentioning
confidence: 99%
“…Benamara ( 2005) used preposition semantics in a cooperative question answering system. In the context of cross-language question answering (CLQA), Hartrumpf, Helbig, and Osswald (2006) used MultiNet to interpret the semantics of German prepositions, and demonstrated that in instances where the answer passage contained a different preposition to that included in the original question, preposition semantics boosted the performance of their CLQA system. Boonthum, Toida, and Levinstein (2006) successfully applied their preposition WSD method in a paraphrase recognition task, namely, predicting that Kim covered the baby in blankets and Kim covered the baby with blankets have essentially the same semantics.…”
Section: Applicationsmentioning
confidence: 99%